S-Embedded subgroups in finite groups - Ballester-Bolinches, A.; Beidleman, J.C.; Feldman, A.D.; Heineken, H.; Ragland, M.F. (Algebra and Discrete Mathematics, 2012)
In this survey paper several subgroup embedding properties related to permutability are introduced and studied.